Nairobi Taxi Driver - Schick, Gerhard (Germany, 2011)
Taking a ride with Kenyan-born Michael Ombok through the heart and the outskirts of Nairobi. He knows the place and he knows Nairobi’s bright side and Nairobi’s dark side. Growing up in a middle-class house, he left his home early to experience both freedom and hunger in the vast slums of the city. After playing guitar with bank robbers and collecting garbage at huge dumping sites, he leaves his familiar surroundings once again to go to study tour-guiding. But yet again, his life takes another turn.
Verzio Film Festival Submission
Keywords: Documentary films